Dynamic Effects of Energy Sector Public Investment on Sectoral Economic Growth: Experience from Pakistan Economy (The Pakistan Development Review, 2014)
The successive economic and financial crisis in recent time has reemphasised the importance of fiscal policy. Modern literature has also revisited the debate regarding the effectiveness of fiscal policy in influencing growth. The issue of the impact of public investment on growth is debated in economic literature since seminal work of Solow (1955). The issue is tackled from different angles. Some have used production function approach [Ligthart (2002), Otto and Voss (1994, 1996), Sturm and de Haan (1995) and Wang (2004)]. Then another seminal work by Aschauer (1989) led a series of work on this issue once again in empirical literature (1989a, 1989b). These approaches used single equation method for estimation and captured only the direct effects of public investment on growth. Periera (2000) gave another twist to this literature by highlighting the indirect effects of public investment on output through its effects on other inputs like private investment and employment. Periera’s works (1999, 2000, 2001, 2003, 2005, 2007 and 2011) also contributed empirically to this literature by using vector autoregressive (VAR) technique. This work accounts for both the direct and indirect effects of public investment on growth and also considers the feedback effects of each input to other and finally their effects on output